Perfil epidemiológico de los accidentes por ofidios. Tena, 2020 en el Hospital “José María Velasco Ibarra” de la provincia de Napo - Llerena Vargas, Henry Leonardo (2020)
The ophidian accident is produced by the bite of snakes that possess and inoculate toxic substances, which injure tissues and cause pathophysiological changes in the victim, causing health consequences. The present investigation called Incidence and severity of ophidian accidents attended at the General Hospital "José María Velasco Ibarra" of Napo province during the period March - August 2020, aims to determine the incidence and severity of ophidian accidents. and identify the main complications of the accidents attended. The research is descriptive, retrospective and transversal; the sample consisted of 27 cases per bite. For the development of the research, data were collected through a technical file, the information of which was obtained from the clinical history of the people who were admitted with an office accident during the study period. During the March-August 2020 period, 27 cases were registered, of which the male gender predominates, in people who are engaged in agricultural activity over 50 years of age. In addition, the cases presented correspond mostly to the parishes of Arosemena tola, Chonta Punta and Cotundo; A large part of the accidents were due to bites in the lower left limb (LIM), which represents 37% of the total cases, in the General Hospital "José María Velasco Ibarra" in the province of Napo, they constitute a significant morbidity, as it has a high incidence, in which most cases are moderate and the most frequent.